Extramedullary plasmacytoma: Tumor occurrence and therapeutic concepts—A follow‐up. (16th May 2022) - Holler, Adrian; Cicha, Iwona; Eckstein, Markus; Haderlein, Marlen; Pöttler, Marina; Rappl, Anja; Iro, Heinrich; Alexiou, Christoph
Abstract: Background: Extramedullary plasmacytoma (EMP) is a solitary tumor consisting of neoplastic plasma cells, with very little to no bone marrow involvement. EMPs are usually located in the head and neck region, but can also occur along the digestive tract, in lungs, or extremities. Methods: Following our publication on EMP, which appeared in 1999 (Cancer 85:2305–14), we conducted a literature search for EMP‐related reports published between 1999 and 2021. The documented cases, as well as 14 of our own patients from the ENT Clinic Erlangen, were extensively analyzed. Results: Between 1998 and 2021, 1134 patients with EMP were reported, for whom information about the tumor localization was available. Among those, 62.4% had EMP in the head and neck area and 37.6% in other body regions. Data on therapy were reported in 897 patients, including 34.3% who received radiation, 28.1% surgery, 22.6% a combination of surgery and radiation, and 15.9% another therapy. In 76.9% patients no recurrence or transformation to multiple myeloma (MM) was reported, 12.8% showed local recurrence and 10.2% developed MM. Radiotherapy alone was associated with a tendency for increased occurrence of MM. In patients with EMP of head and neck area, combination therapy (surgery and radiation) resulted in a 5‐year overall survival rate of 98.3%, surgery alone of 92.4%, and radiotherapy of 92.7%. Conclusions: Collectively, our analyses indicate that surgical resection alone can achieve long‐term tumor control in patients with EMP, if the tumor can be removed within safe limits without causing serious functional impairment. However, if this is not certain, either radiation or a combination of surgery and radiation therapy is suggested as an effective means of local tumor control. Abstract : This paper provides an overview of the extramedullary plasmacytoma cases reported between 1999 and 2021. The global patients' cohort and the current therapy options are compared to our previous report from 1999.